The new Italian Code of Medical Ethics - Sgreccia, Elio (Medicina e Morale, 1989)
The presentation of the new Italian Code of Medical Deontology would require a broad and comparative consideration with the previous text issued by the National Federation of Medical Boards in 1978, to note the points of development in these ten years, in which new problems and new demands have emerged in the world of medical culture and science.